Genetically modified microorganisms for agricultural use: an opportunity for the advancement of risk assessment criteria in Argentina - Rubinstein, Clara; Levitus, Gabriela; Vicien, Carmen; Modena, Natalia Andrea; Ruzal, Sandra; Vesprini, Facundo; Lewi, Dalia Marcela; Caminoa, Cecilia; Malacarne, Maria Fabiana; Francescutti, Nerina; Amaturo, Juan Ignacio (Frontiers in Bioengineering and Biotechnology, 2025)
The development and use of biologicals in agriculture is of growing interest globally. The potential of these tools to increase and protect yield complementing other tools has stimulated the interest of developers. Agricultural countries like Brazil and Argentina in Latin America have extensive experience with the use of biologicals for biocontrol and as seed inoculants. The last decade has seen the number of bio-based startups grow in the region, many of those dedicated to the development of microbial based bio-inputs. The potential for improving the efficacy and functionality of these products by means of gene technologies is very promising; however, the regulatory oversight of these innovations needs adaptation to become fit for purpose. The Biotechnology Working Group at ICCAS identified the need for a science-based discussion on this matter and considered alternatives to the current paradigm, developed over 30 years ago for transgenic plants.